2019
DOI: 10.1016/j.ijcard.2018.07.103
|View full text |Cite
|
Sign up to set email alerts
|

Religion and spirituality as predictors of patient-reported outcomes in adults with congenital heart disease around the globe

Abstract: Religiosity/spirituality is an independent predictor for some PROs, but has differential impact across countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 26 publications
1
28
0
4
Order By: Relevance
“…Socio‐demographic data were collected by self‐reports and information on medical history was retrieved by chart reviews. Details on the methodology of APPROACH‐IS have been provided in a methods paper , and numerous papers have described findings obtained from this global sample or from patients from specific countries or regions .…”
Section: Approach‐ismentioning
confidence: 99%
“…Socio‐demographic data were collected by self‐reports and information on medical history was retrieved by chart reviews. Details on the methodology of APPROACH‐IS have been provided in a methods paper , and numerous papers have described findings obtained from this global sample or from patients from specific countries or regions .…”
Section: Approach‐ismentioning
confidence: 99%
“…In the past three decades, tremendous progress in patient's management has significantly improved the overall prognosis, and, consequently, transferred the mortality in CHD from childhood to adulthood . As a result, after focusing on the survival of children with CHD, more attention is currently being given to health‐related quality of life and psychological well‐being of the children and their parents . Indeed, despite these great advances, psychological trauma is not uncommon for CHD survivors .…”
Section: Introductionmentioning
confidence: 99%
“…When considering the impact of CHD diagnosis on the parental psychological state, some studies stated that posttraumatic stress disorders were observed in more than 30% of the parents, with major depressive episodes in 25%‐50% of cases . The psychological well‐being of the parents has been considered as a major factor influencing the psychological state of the expected child, sometimes above the CHD severity itself .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations